Vendors as Environmental Stakeholders: Lessons from a Regional Sports Event event - Joo-Ee Gan (Centre For Tourism Planning and Development, 2020)
This paper examines the impact of vendor management on the recycling programme of a regional sports event. Guided by the theory of planned behaviour (TPB) and the norm activation model (NAM), the organizer's leverage strategies were qualitatively assessed for their effectiveness in promoting vendor recycling behaviour. The findings identified vague selection criteria, unclear expectations, limited engagement, the lack of communication and poor coordination as weaknesses in the organizer's leverage strategies. In particular, the altruistic strategy of information dissemination